Studies on Schismatoglottideae (Araceae) of Borneo LVIII : Further novelties described for the genus Piptospatha, and a note on Piptospatha Sect. Gamogyne - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2016)
Piptospatha bella S. Y. Wong & P. C. Boyce and Piptospatha lurida S. Y. Wong & P. C. Boyce are described and illustrated from Sarawak, Malaysian Borneo. Their recognition takes Piptospatha to 18 described species. Piptospatha lurida is most similar to P. burbidgei, a species formerly allotted its own genus, Gamogyne, later made into a section of Piptospatha. Notes on Gamogyne are provided and a correction to published information on the placentation of Gamogyne offered.